Distribution mapping of smaller arachnid orders and Pseudoscorpiones in Malaysia - Faris Adly; Dzulhelmi Muhammad Nasir; Nur-Athirah Abdullah; Suriyanti Su; Nurul Fatihah Abd Latip; Madihah Halim; Faszly Rahim (Jurnal Entomologi Indonesia, 2022)
This checklist serves as a basic information based on compilation from published literatures, internet database and from specimens’ collection stored at Center of Insect Systematics Universiti Kebangsaan Malaysia. To date, this study compiled smaller arachnids (28 species) and Pseudoscorpiones (41 species) that had been recorded in Malaysia. Although smaller arachnid orders were concentrated at localities with average rainfall and humidity,  Pseudoscorpiones can be found at both wet and dry environments. More work is needed to determine the species diversity and distribution of these cryptic group.